Utilization Of Jackfruit (Artocarpus Heterophyllus Lam.) Rind Powder As Value Added Ingredient In Bread - Feili, Reza (2014)

(untitled)
The main objectives of this study were to develop jackfruit-based high fiber bread by utilizing jackfruit rind powder in bread formulation, and to characterize physical, functional, chemical and sensory properties of produced high fibre bread. Jack fruit rind pieces were treated with a few soaking and washing steps prior to drying and milling treatments. Objektif utama kajian ini adalah untuk membangunkan roti berserat tinggi berasaskan nangka (Artocarpus heterophyllus Lam.) dengan menggunakan serbuk kulit nangka dalam pembuatan roti, dan menilai ciri-ciri fizikal, berfungsi, kimia dan sifat sensori roti berserat tinggi yang dihasilkan. Kulit buah nangka telah diolah dengan beberapa langkah perendaman dan pencucian sebelum dikeringkan dan digiling.